Primary debulking surgery or neoadjuvant chemotherapy followed by interval debulking surgery for patients with advanced ovarian cancer - Zheng, Hong; Gao, Yu-Nong (Chinese Journal of Cancer Research; Vol 24, No 4 (December 07, 2012): Chinese Journal of Cancer Research, 2012)
Objectives: To compare the survival and perioperative morbidity between primary debulking surgery (PDS) and neoadjuvant chemotherapy followed by interval debulking surgery (NAC/IDS) in treating patients with advanced epithelial ovarian cancer (EOC). Methods: We retrospectively reviewed 67 patients with stage IIIC or IV EOC treated at Peking University Cancer Hospital from January 2006 to June 2009. Wherein, 37 and 30 patients underwent PDS and NAC/ IDS, respectively. Results: No difference in overall survival (OS) or progression-free survival (PFS) was observed between NAC/IDS group and PDS group (OS: 41.2 vs. 39.1 months, P=0.23; PFS: 27.1 vs. 24.3 months, P=0.37). The optimal debulking rate was 60% in the NAC/IDS group, which was significantly higher than that in the PDS group (32.4%) (P=0.024). The NAC/IDS group had significantly less intraoperative estimated blood loss and transfusion, lower nasogastric intubation rate, and earlier ambulation and recovery of intestinal function than the PDS group (P